Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/s40473-019-00174-5
|View full text |Cite
|
Sign up to set email alerts
|

Galantamine-Memantine Combination as an Antioxidant Treatment for Schizophrenia

Abstract: Purpose of Review-The objective of this article is to highlight the potential role of the galantamine-memantine combination as a novel antioxidant treatment for schizophrenia.Recent Findings-In addition to the well-known mechanisms of action of galantamine and memantine, these medications also have antioxidant activity. Furthermore, an interplay exists between oxidative stress, inflammation (redox-inflammatory hypothesis), and kynurenine pathway metabolites. Also, there is an interaction between brain-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 239 publications
(205 reference statements)
0
27
0
Order By: Relevance
“…GAL has an antioxidant activity related with the enolic OH group [6]. One of the mechanisms by which GAL improves the mental function in Alzheimer's dementia is thought to be its antioxidant effect [49][50][51]. CU also is a proven antioxidant and brain protector [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…GAL has an antioxidant activity related with the enolic OH group [6]. One of the mechanisms by which GAL improves the mental function in Alzheimer's dementia is thought to be its antioxidant effect [49][50][51]. CU also is a proven antioxidant and brain protector [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…This integrative pharmacology approach (Collis, 2006; Geerts et al, 2020; Gribkoff & Kaczmarek, 2017; Koola, 2019a; Koola et al, 2014) may be applicable to other combination treatments targeting glutamatergic‐nicotinergic systems concurrently as shown in Table 2. The combination of glutamatergic‐nicotinergic medications may target the quintuple hypotheses (dopamine‐nicotinic/cholinergic‐glutamate/NMDA‐GABA‐kynurenic acid [KYNA], Koola, 2018a) and improve the antioxidant biomarkers (Koola et al, 2019) as shown in Figure 1. The combination treatment may improve positive, cognitive, and negative symptoms of schizophrenia (Koola, 2018a; Koola et al, 2019).…”
Section: Potential Combination Treatments In Schizophreniamentioning
confidence: 99%
“…The combination of glutamatergic‐nicotinergic medications may target the quintuple hypotheses (dopamine‐nicotinic/cholinergic‐glutamate/NMDA‐GABA‐kynurenic acid [KYNA], Koola, 2018a) and improve the antioxidant biomarkers (Koola et al, 2019) as shown in Figure 1. The combination treatment may improve positive, cognitive, and negative symptoms of schizophrenia (Koola, 2018a; Koola et al, 2019). Finally, the combination also may stabilize other major pathophysaiological mechanisms (including the KYNA‐centric pathophysiology [Koola, 2020]) and biomarkers as shown in Figures 1–3.…”
Section: Potential Combination Treatments In Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations